Burnout in Obstetrics and Gynecology Residents: A National Survey. (October 2015) - Park, Kenneth; Jiang, Xuezhi; O'Sullivan, David M.; Schnatz, Peter F.
Abstract : BACKGROUND: Residency training is associated with a significant degree of burnout in single institution studies. OBJECTIVE: To assess the rate of burnout in a national sample of obstetrics and gynecology residents. METHODS: A web link to a 50-item, online, nonobligatory survey was distributed to all Accreditation Council for Graduate Medical Education–accredited obstetrics and gynecology residents through program coordinators and directors. The survey was open for responses from March 11, 2014 to June 5, 2014. RESULTS: Of 892 who responded to the survey, 790 (88.6%) were valid for analysis. Of 790, 26% were noted to have high burnout. Residents with burnout also had higher rates of depression and anxiety ( P <.001). There were no statistically significant differences in burnout between men and women, single compared with married, university compared with nonuniversity programs, and size of programs (more than 20 compared with 20 or fewer residents). Burnout rates were not associated with either the number of children or year of training. However, burnout rates were higher for residents who worked more than 70 hours/week. Residents with burnout felt there was a lack of "strong support" by the faculty ( P =.001) and fellow residents ( P =.006), that faculty were not committed to teaching ( P <.001), perceived a greater emphasis on "service over education" ( P <.001), and were less satisfied with the hospital's benefits and facilities ( P =.023). Furthermore, as frequency of poor clinical outcomes increased, the severity of the depression also increased ( P =.021). CONCLUSION: Nationally, about 25% of obstetrics and gynecology residents have high burnout. It is important to recognize factors associated with burnout in residents, so we may institute changes to better accommodate our future physicians and assure patient safety.